An evaluation of dexterity and cutaneous sensibility tests for use with medical gloves. (October 2016) - Mylon, Peter; Lewis, Roger; Carré, Matt J; Martin, Nicolas
The ability of selected dexterity and cutaneous sensibility tests to measure the effect of medical glove properties (material, fit, and number of layers) on manual performance was analyzed. Manual performance testing of gloves to-date has focused on thicker gloves where the effects are more obvious. However, clinicians have reported dissatisfaction with some medical gloves and a perceived detriment to performance of new materials compared to latex. Three tests (Purdue Pegboard Test, Crawford Small Parts Dexterity Test, and Semmes-Weinstein Monofilaments) were performed by 18 subjects in five hand conditions (ungloved; best-fitting, loose-fitting and a double layer of latex examination gloves; best-fitting vinyl gloves). Tests were performed in the ungloved condition first, and the order of the gloved tests was randomized. Learning behavior was also measured. The Purdue test showed a significant effect of hand condition, but no differences between latex and vinyl. No significant effect of hand condition was found in the Crawford "Pins and Collars" test, but the "Screws" test showed promising discrimination between glove types. The Monofilaments test showed a significant effect of hand condition on cutaneous sensibility, particularly a reduction when "double-gloving, " but no significant differences between glove types. Existing tests show some ability to measure the effect of gloves and their properties on manual performance but are not comprehensive and require further validation. In order to fully describe the effects of medical gloves on manual performance, further tests should be designed with greater resolution and that better replicate clinical manual tasks.